The governance of the family business from the perspective of agency and stewardship theory - TAJER, Abdellah; ARABAN, Oumaima; ESSABBAR, Hicham; RIGAR, Sidi Mohamed (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Common to many research studies on the governance of family firms, they often rely on classical theories to explain and show their distinctive features. In particular, agency theory and stewardship theory. Although these two theories both address the same phenomena, namely behaviors at the individual level and governance mechanisms at the corporate level, many researchers treat these two theories as two distinct and opposing theoretical fields for the family business. As well, these two theoretical streams have been widely used to examine a myriad of issues within family firms. In this regard, the purpose of this research is to present a review of the theoretical and empirical literature of these two streams in order to understand the behavior of agents, governance, and unique aspects of family firms.